One Health Surveillance of Antimicrobial Resistance Phenotypes in Selected Communities in Thailand - Duangdao Sudatip; Surapee Tiengrim; Kittipong Chasiri; Anamika Kritiyakan; Wantanee Phanprasit; Serge Morand; Visanu Thamlikitkul (MDPI AG, 2022)
Integrated surveillance of antimicrobial resistance (AMR) using the One Health approach that includes humans, animals, food, and the environment has been recommended by responsible international organizations. The objective of this study was to determine the prevalence of AMR phenotypes in Escherichia coli and Klebsiella species isolated from humans, pigs, chickens, and wild rodents in five communities in northern Thailand. Rectal swabs from 269 pigs and 318 chickens; intestinal contents of 196 wild rodents; and stool samples from 69 pig farmers, 155 chicken farmers, and 61 non-farmers were cultured for E. coli and Klebsiella species, which were then tested for resistance to ceftriaxone, colistin, and meropenem. The prevalence of ceftriaxone-resistant E. coli and Klebsiella species in pigs, chickens, rodents, pig farmers, chicken farmers, and non-farmers was 64.3%, 12.9%, 4.1%, 55.1%, 38.7%, and 36.1%, respectively. Colistin resistance in pigs, chickens, rodents, pig farmers, chicken farmers, and non-farmers was 41.3%, 9.8%, 4.6%, 34.8%, 31.6%, and 24.6%, respectively. Meropenem resistance was not detected. The observed high prevalence of AMR, especially colistin resistance, in study food animals/humans is worrisome. Further studies to identify factors that contribute to AMR, strengthened reinforcement of existing regulations on antimicrobial use, and more appropriate interventions to minimize AMR in communities are urgently needed.